Synergistic Effects of 2-Deoxy-D-Glucose and Cinnamic Acid with Erlotinib on NSCLC Cell Line - Wrood salim Al-khfajy; Munaf Hashim Abdulrazzaq; Zakariya Al-Mashhadani (College of Pharmacy University of Baghdad, 2023)
Background: In spite of all efforts, Non-small cell lung cancer (NSCLC) is a fatal solid tumor with a poor prognosis as of its high metastasis and resistance to present treatments. Tyrosine kinase inhibitors (TKI) such as erlotinib are efficient in treating NSCLC but the emergence of chemoresistance and adverse effects substantially limits their single use. Objective: in this study, the combination treatments of either 2-deoxy-D-glucose (2DG) or cinnamic acid (CINN) with erlotinib (ERL) were tested for their possible synergistic effect on the proliferation and migration capacity of NSCLC cells. Methods: In this study, NSCLC model cell line A549 was used to investigate the effects of single compounds and their combination on cell growth inhibition, clonogenic potential, and migration capacity. Next, the Combination index (CI) and the Dose-Reduction Index (DRI) were determined to determine the nature of the drug's combination and to measure how many folds the dose could be lowered for each drug in a synergistic combination. Results: the combination treatment demonstrated more significant inhibition of viability of A549 cells compared to individual therapy. Our data show that CINN augments the sensitivity to erlotinib in all doses tested. The combination of 2DG or CINN with erlotinib also reduced the clonogenicity of NSCLC cells up to 67% and 85%, respectively, as compared to the erlotinib single treatment. Furthermore, CINN +ERL decreased the migratory ability of A549 cells by 3-fold and further induced much more apoptotic cell death phenotypes. Conclusion: in summary, co-administration of 2DG or cinnamic acid with erlotinib increases the inhibitory effects of erlotinib on NSCLC cell tumorigenicity and migration.